Stainless steels in architecture, building and construction : Guidelines for corrosion prevention. (Nickel Development Institute reference book series ;, 2001)
Stainless steel is one of the most durable materials used in architecture, building, and construction. With appropriate grade and finish selection, design, fabrication, and maintenance, the appearance and properties of the stainless steel will remain unchanged over the life of the building. These properties make stainless steel a popular choice for buildings designed to last 100 or more years, aggressive environments, applications where security is a concern, and high traffic areas. Atmospheric corrosion, tarnishing, pitting, crevice corrosion, embedded iron, erosion/corrosion, galvanic corrosion, and stress corrosion cracking can impact the performance and appearance of building materials. This brochure discusses these issues and stainless steels performance relative to other construction materials. --